KEBIJAKAN NASIONAL TENTANG MUTU PEKERJA SOSIAL - Chazali H. Situmorang (Jurnal Manajemen Pendidikan, 2010)
This research is aimed to analyse : (1) Policy substance which is guiding the social workers, especially related to the quality of the social workers, (2) The policy implementation which is implemented by the stakeholders of the social ministry (The directorate General of social rehabilitation services, The head of Research and training Board, The head of Employee and organization Biro, All directors and heads of Training and education centers, (3) and the result of policy implementation which is done in the operational level. The resources of the primary data as an anlysis unit is the stakeholders of social ministry, social workers and the head of care management centers in the local and central government. The conclussion of this research is : (1) The National Policy in the form of regulation (Constitution, government President and Minister regulation), (2) In the policy implementation of the social workers’ quality, during the five year period (2004-2009) has not been implemented well. (3) The Evaluation of national policy implementation about the quality of the social workers in providing social services is : (a) 40% of the social workers who are competence in providing social services, (b) the qualification of social workers mostly in the skilled level ( 65 %) and the small part is in the expert level (35 %), (c) The ratio of social workers to the clients is about 1 : 22 (1156 social workers handle 25.000 clients), (d) the limited number of social workers and budget, lack of training and education are regarded as the causes of the low target of social services and the low quality of the the PMKS output, (4) There are some head of the care management center who do not give the sufficient opportunities for the social workers to implement their main job and function. This problem brings bad impact to the performance and competencies of the social workers in developping their profession.